Analysis of the Influence of Financial Literacy and Financial Inclusion on MSME Performance - Adi Adiansyah; Asri Solihat; Lindayani Lindayani (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
This research is motivated by the fact that the majority of MSMEs in Garut Regency are micro-sized, representing 86%. The purpose of this study is to determine the influence of financial literacy, financial inclusion, and financial management on the performance of MSMEs in Garut Regency. The research method used is descriptive analysis using SEM-PLS, where the analysis used in this study is the outer model test, the inner model test, and the hypothesis test carried out by determining the r-square, f-square, and t-statistic values. The sample in this study was 100 MSMEs in Garut Regency registered as MSMEs with NIB (Entrepreneurship Identification Number). The findings of this study indicate that financial literacy does not significantly influence MSME performance. Meanwhile, financial inclusion and financial management have a significant positive effect.